Advancing age is associated with more impaired mediolateral balance control after step down task - Buková, Alena; Kováčiková, Zuzana; Sarvestan, Javad; Neumannová, Kateřina; Pecho, Juraj; Zemková, Erika (Gait & posture, 2023)
BACKGROUND: To prevent the risk of stair descent falls and associated injuries in the older adults, it is important to understand the factors that affect this frequent locomotion of daily living. The fact that falls are in most cases the result of the interaction between intrinsic and extrinsic factors is very often underestimated when designing test protocols. RESEARCH QUESTION: This study aimed at evaluating balance control during and immediately after step down onto an unstable surface. METHODS: Physically active men and women aged 60-69 years (n = 28) and 70-79 years (n = 18) were asked to perform a step down onto a foam pad and stand still for 30 s (restabilization phase). Centre of pressure (CoP) velocity and standard deviation of CoP sway in anteroposterior and mediolateral direction were evaluated during the step down (CoP VAP, CoP VML, CoP SDAP, CoP SDML) and in the first 5 s of restabilization (CoP VAP5, CoP VML5, CoP SDAP5, CoP SDML5). In addition, time to complete step was investigated. RESULTS: Participants aged 70-79 years presented worse ML balance control after step down onto an unstable surface than their younger counterparts. This was represented by the significantly higher values of CoP SDML5 and CoP VML5 (p = 0.022 and p = 0.017). No other significant differences were detected. SIGNIFICANCE: Age is associated with a more significant ML center of pressure velocity and sway after step down onto a foam pad in physically active older adults. Exercises aimed at improving ML balance control in unstable conditions should be the subject of physical interventions even in older adults with overall good state of health and physical fitness.
Keywords: fyzikální vyšetření; ženské pohlaví; terapie cvičením; Physical Examination; lidé; lokomoce; senioři; mužské pohlaví; Female; cvičení; Male; Exercise; Aged; Exercise Therapy; Locomotion; Postural Balance; posturální rovnováha; Humans